La cultura organizacional, pilar fundamental de la calidad en las instituciones de educación superior de la provincia de Cotopaxi. Diseño de un modelo de comportamiento organizacional por competencias. - Cárdenas Rubio, Silvia Esther (2016)
The investigation began in the Institutions of Higher Education of Cotopaxi, this project constitutes as a tool for change of the organizational culture and adaptation for the future, for which a descriptive investigation was carried out where we determined the adequate sample of a population of authorities, teachers, employees, workers and students, for the collection of information, the survey was applied as a technique through a questionnaire. Coming to the conclusion that the organizational culture does affect the good performance and quality of the organization, in turn it is recommended that managers must face the challenge of changing that set of values, beliefs and customs that guide the behavior of their collaborators. in order to develop new innovative strategies.